Zachary Taylor - Eisenhower, John S. D., 1922-2013 (American presidents, 2008)
A profile of the twelfth president traces his rise in the military and successes in the Mexican war to his election as the first president without a prior political office, in an account that also offers insight into Taylor's views on slavery and his sudden death.